Analisis SWOT Pengolahan Makanan Pada Katering di Kecamatan Simokerto Surabaya Tahun 2019 - Sharen Liestya Santosa; Narwati .; Ernita Sari (Poltekkes Kemenkes Surabaya, 2020)
Jasaboga in producing food must pay attention to the quality of food to improve food quality need to process food that is in accordance with the requirements of food sanitation hygiene. So the purpose of this study is to assess the application of food processing to catering in Simokerto Subdistrict where the components of food processing such as food processing, food processing, food equipment, and food handlers are then analyzed using SWOT Analysis (Strength, Weakness, Opportunity, and Threats). The results of the SWOT analysis will produce a Food Processing Development Strategy for Catering. This research is descriptive with research design using evaluation design with the aim of the results of this study used for improvement or improvement of activities / programs in catering. The location of the study was carried out in 3 catering in Surabaya Simokerto sub-district, using sampling techniques Total Sampling Technique. The research activity used an observation sheet to obtain data on the application of food processing at the catering district of Simokerto Surabaya. Based on the results of the study, Food Processing catering in Simokerto Surabaya District in general is good and according to existing regulations such as Food Processing Places has a Good category of 78%, Food Processing has a Good category of 67%, Food Handlers have a Good category of 72% while Cookware has a sufficient category of 64% so that repairs need to be done. In improving catering food processing can be done by utilizing the strengths and opportunities that exist among them by conducting routine monitoring of the health center, counseling on food safety and food processing methods that are good and right, and for catering in Simokerto sub-district can implement the recommended development strategy to innovate on a variety of menus to increase consumer purchasing power, take advantage of technological advance as a media for promotion and register catering to health services to obtain Jasaboga sanitary hygiene certificates.Keywords: Food processing, SWOT Analysis and Food Processing development strategy